2014
DOI: 10.1177/0888406414525048
|View full text |Cite
|
Sign up to set email alerts
|

How Are They Now? Longer Term Effects of eCoaching Through Online Bug-In-Ear Technology

Abstract: Abstract:In this study, using mixed methods, we investigated the longer term effects of eCoaching through advanced online bug-in-ear (BIE) technology. Quantitative data on five dependent variables were extracted from 14 participants' electronically archived video files at three points in time-Spring 1 (i.e., baseline, which was the first semester of enrollment without eCoaching feedback), Spring 2 (i.e., 1 year later with eCoaching feedback), and Spring 3 (i.e., 2 years later after exiting the program without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 30 publications
5
48
0
Order By: Relevance
“…Further, social validity data from three BIE studies indicate BIE coaching is helpful in increasing student performance with school-age students. In one study, educators reported improvements in students' persistence during difficult tasks (Scheeler et al, 2010) and in two studies, observations of students' behaviors indicated improved engagement during lessons (Rock et al, 2009(Rock et al, , 2014. However, another of Rock and colleagues' (2012) studies found nonsignificant effects of BIE on student engagement.…”
Section: Social Validity Of Bug-in-ear Coachingmentioning
confidence: 88%
See 1 more Smart Citation
“…Further, social validity data from three BIE studies indicate BIE coaching is helpful in increasing student performance with school-age students. In one study, educators reported improvements in students' persistence during difficult tasks (Scheeler et al, 2010) and in two studies, observations of students' behaviors indicated improved engagement during lessons (Rock et al, 2009(Rock et al, , 2014. However, another of Rock and colleagues' (2012) studies found nonsignificant effects of BIE on student engagement.…”
Section: Social Validity Of Bug-in-ear Coachingmentioning
confidence: 88%
“…Preservice special educators have reported that BIE aided in the acquisition of evidence-based practices during coaching sessions, which led to their spontaneous use of practices when coaching was not provided (Rock et al, 2014). Further, social validity data from three BIE studies indicate BIE coaching is helpful in increasing student performance with school-age students.…”
Section: Social Validity Of Bug-in-ear Coachingmentioning
confidence: 95%
“…Although the immediate feedback offered by BIE technology has been praised in recent research (Ottley & Hanline, 2014;Rock et al, 2012;Rock et al, 2014;Wade, Bohac, & Platt, 2013), some teachers and coaches complain that the two sets of verbal stimuli can be overwhelming while trying to deliver instruction. A novice teacher may struggle more with the added stimuli of coaching via BIE (Smith & Israel, 2010).…”
Section: Bug-in-earmentioning
confidence: 99%
“…Recently, researchers have begun using technology to provide real-time performance feedback privately or at a distance using bug-in-ear systems or Internetbased video conferencing software to provide performance feedback at a distance (Goodman, Brady, Duffy, Scott, & Pollard, 2008;Machalicek et al, 2010;Ploessl & Rock, 2014;Rock et al, 2012;Rock et al, 2009;Rock et al, 2014;Scheeler et al, 2010 paired video conferencing with bug-in-ear to provide private feedback to teachers who responded with improved instructional practices. Researchers have also had positive effects using similar, real-time feedback in person using bug-in-ear systems to provide feedback privately to teachers during instruction (e.g., Goodman et al, 2008) Agent.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, researchers may examine remote applications of real-time VPF by providing it remotely using Internet-based video-conferencing software; this is an extension of immediate performance feedback research that has allowed researchers to provide the bug-in-ear interventions to teachers in distant locations (e.g., Rock et al, 2014;Scheeler et al, 2011).…”
Section: Limitations and Future Researchmentioning
confidence: 99%